2019
DOI: 10.1111/dom.13614
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and harms of long‐acting insulins for type 1 and type 2 diabetes: A systematic review and meta‐analysis

Abstract: Aim: To review evidence comparing benefits and harms of long-acting insulins in patients with type 1 and 2 diabetes.Methods: MEDLINE and two Cochrane databases were searched during February 2018. Two authors selected studies meeting inclusion criteria and assessed their quality. Comparative studies of adult or paediatric patients with diabetes treated with insulin degludec, detemir or glargine were included. Meta-analysis was used to combine results of similar studies, and the I 2 statistic calculated to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 82 publications
(300 reference statements)
0
20
0
Order By: Relevance
“…CI Confidence interval, PYE patient-year, RR rate ratio, T1D/T2D type 1/type 2 diabetes mellitus with a minimal increase in body weight. The very modest, though significant, increase in body weight in patients with T1D is not consistent with trial results [33]. Speculative explanations include: (1) the prior use of detemir, which is associated with less weight gain, in a subset of patients; (2) the correction of a relative hypo-insulinization with the prior basal regimen; (3) differences in the induction of satiety.…”
Section: Discussionmentioning
confidence: 83%
“…CI Confidence interval, PYE patient-year, RR rate ratio, T1D/T2D type 1/type 2 diabetes mellitus with a minimal increase in body weight. The very modest, though significant, increase in body weight in patients with T1D is not consistent with trial results [33]. Speculative explanations include: (1) the prior use of detemir, which is associated with less weight gain, in a subset of patients; (2) the correction of a relative hypo-insulinization with the prior basal regimen; (3) differences in the induction of satiety.…”
Section: Discussionmentioning
confidence: 83%
“…degludec vs glargine), as already stated. Current evidence does not support any difference in change in body weight between these two insulins, therefore the overall results of our meta-analysis evaluating changes in body weight following the addition of GLP-1RA to SGLT2i should not be affected by the trial design and data of DUAL IX 29 .…”
Section: Discussionmentioning
confidence: 87%
“… 56 In a recent meta-analysis including patients with T1D and T2D, those receiving insulin detemir gained less body weight than those given degludec or Glar-100. 57 Another systematic review concluded there was less weight gain with basal insulin analogues detemir and Glar-300 compared to Glar-100 and degludec but with a low quality of evidence. 58 Therefore, in the case of obesity and T1D, switching long-acting insulin to either detemir or Glar-300 could be somewhat useful to prevent weight gain.…”
Section: Treatment Of Obesity In T1d: Challenges and Opportunitiesmentioning
confidence: 99%